2011
DOI: 10.1021/nn202294b
|View full text |Cite
|
Sign up to set email alerts
|

Capture, Store, and Discharge. Shuttling Photogenerated Electrons across TiO2–Silver Interface

Abstract: UV irradiation of TiO(2) nanoparticles in the presence of Ag(+) ions results in the quantitative reduction and deposition of silver on its surface. Continued UV irradiation following the deposition of Ag on the TiO(2) surface causes a blue shift in the surface plasmon peak from 430 to 415 nm as these particles become charged with excess electrons. Under UV irradiation, both the charging and discharging of electrons occur at different rates, thus allowing the system to attain a steady state. Upon stopping the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
271
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(282 citation statements)
references
References 50 publications
7
271
1
3
Order By: Relevance
“…Nevertheless, the true role of noble metal nanoparticles in such systems remains the subject of debates. [160] For one reason, the reported enhancements due to the plasmonic effect were limited. Furthermore, how the introduction of metal to a semiconducting light absorber influences the nature of the metal-semiconductor junction can be complicated.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Nevertheless, the true role of noble metal nanoparticles in such systems remains the subject of debates. [160] For one reason, the reported enhancements due to the plasmonic effect were limited. Furthermore, how the introduction of metal to a semiconducting light absorber influences the nature of the metal-semiconductor junction can be complicated.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…However, in these recent metal-TiO2 Schottky diode structures [37][38][39][40][41][42][43][44][45][46][47], it would appear that the barrier layer was actually quite a bit thicker than 10 nm (probably in excess of 1 um) and further details was unable to be found in these papers. Semi-classical models did not account for non-equilibrium energy distributions of carriers, or do so through a localize lattice temperature.…”
Section: Theoretical Modeling Of Ag-tio2-ti Mim Diodesmentioning
confidence: 98%
“…First, Tatsuma et al [37,38,45] and other workers [42,46] proposed that the photoexcited electrons in the metal nanoparticles transferred from the metal particle to the TiO2 conduction band since the photoresponse of these metal-TiO2 diode structures was consistent with the absorption spectra of Au or Ag nanoparticles. Second, Kamat et al [43,44] and Li et al [47] have suggested that the noble metal nanoparticles act as electron sinks or traps in the metal-TiO2 diode structures to accumulate the photogenerated electrons, which could minimize charge recombination in the semiconductor films. Obviously, a better understanding of these effects is crucial in exploiting the beneficial aspects of metal nanoparticles in photovoltaics.…”
Section: Review Of Metal-insulator-metal (Mim) Diodesmentioning
confidence: 99%
“…Further as the silver content increases on the surface of the photocatalyst, the surface area available for photon absorption decreases thereby decreasing the rate of photogeneration of electron-hole pair. The photocatalytic activity decreases with increase in the silver content above the optimum level [48,49]. Addition of the electron acceptors such as HP and APS to the reaction mixture is one of the strategies employed to decrease the rate of electron-hole recombination process.…”
Section: Photodegradation Of Rsmentioning
confidence: 99%